Cities in transition: Krakow‘s social, economic and spatial transformation within the last thirty years (selected aspects) - Anna Karwińska; Dorota Jopek; Michał Kudłacz; Michał Wiśniewski (Acta Polytechnica CTU Proceedings)
Krakow is a city that has undergone an immense transformation in recent years. At the end of the 1980s, the period of communism ended and Polish local governments began to operate based on the principles of subsidiarity, decentralisation and independence. In 2004, Poland joined the European Union, which opened up new prospects for development, including in regional and local terms. The world has become a networked and digitized entity susceptible to the influence of innovation. Due to metropolitisation processes, cities, especially those offering above-average earnings, a diversification of economic resources and a relatively high quality of life, began to develop even more dynamically, which had and still has negative consequences. In Poland, there are five cities in which development dynamics have a highly specific dimension. Apart from the capital city of Warsaw, these are Krakow, Wrocław, Poznań and the agglomeration of the so-called Tri-city (Gdańsk, Sopot and Gdynia). The aim of this study is to show how Krakow, the second-largest city in Poland, has evolved over the last three decades at the level of demographics, urban development and economy; how it changed in the historical “milestones” indicated above. Therefore, depending on the availability of statistical data, several time periods were selected and compared with each other in the most important areas of Krakow’s functioning. The research hypothesis is as follows: Krakow’s development policy in key areas optimally uses the opportunities resulting from contextual conditions (social, economic and cultural changes that have taken place in recent decades). The study focuses on the three main problems of the city’s development (the abovementioned key areas of the city’s functioning and development): socio-demographic, spatial and economic changes. The analysis assessed data from the literature, city reports and other available sources, as well as public quantitative data (assessment of data from the National Census for the years 1988, 2002, 2011, 2022; Local Data Bank of Statistics Poland and other repositories and reports).